2007
DOI: 10.1007/s12088-007-0068-9
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Escherichia coli O157:H7 by cinnamon extracts in carrot-kinnow mandarin blends

Abstract: We investigated the antimicrobial effi cacy of cinnamon extracts in laboratory prepared Kinnow-mandarin carrot blends challenged with Escerichia coli O157:H7. Freshly squeezed carrot and kinnow-mandarin juices were mixed to obtain a typical blend, inoculated with E. coli O157:H7 cultures at 10 2 CFU/mL with and without cinnamon extracts (0.3%) and stored at 4, 8 and 28 o C for up to 10 hours. Counts on tryptic soy agar (TSA) selective medium (Mac conkey sorbitol agar) and thin agar layer (TAL) were determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
(10 reference statements)
0
0
0
Order By: Relevance
“…that E. coli O 157 :H 7 counts decreased dramatically from 4.9x10 6 to 1.0x10 2 CFU/ml in the presence of 500 μg/ml of the purified from cinnamic aldehyde Moushumi, et al (2007). showed that 0.3% cinnamon extract reduce 2 log 10 CFU/ml E. coli O 157 :H 7 in carrot blend at 4ºC.…”
mentioning
confidence: 87%
“…that E. coli O 157 :H 7 counts decreased dramatically from 4.9x10 6 to 1.0x10 2 CFU/ml in the presence of 500 μg/ml of the purified from cinnamic aldehyde Moushumi, et al (2007). showed that 0.3% cinnamon extract reduce 2 log 10 CFU/ml E. coli O 157 :H 7 in carrot blend at 4ºC.…”
mentioning
confidence: 87%